1997
DOI: 10.1111/j.0022-3646.1997.00764.x
|View full text |Cite
|
Sign up to set email alerts
|

BIOMASS AND DYNAMICS OF GROWTH OF ULVA SPECIES IN PALMONES RIVER ESTUARY1

Abstract: During the last decade, the Palmones River estualy has undergone severe eutrophication followed by a green tide episode; two species ofUlva, rotundata Blid. and Ulva curvata (Kutz.) De Toni, were the main macroalgae responsible for this bloom. From November 1993 to December 1994, we followed the biomass, the growth dynamics, and tissue elemental composition (C:N:P) of Ulva species, as well as some physicochemical variables in the estualy. Maximum biomass (up to 375 g dly wt.m-2 in some spots, corresponding to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
81
0
2

Year Published

2001
2001
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 137 publications
(93 citation statements)
references
References 33 publications
5
81
0
2
Order By: Relevance
“…Bird grazing takes place mainly during the late summer and autumn when the difference between sites is already evident; thus we assume that grazing was also not responsible for the observed difference. Several authors have suggested the importance of wind and currents as important factors for transport of free-floating macroalgae Hernández et al 1997;Salomonsen et al 1997). In the Veerse Meer, transport from the more exposed site at Kwistenburg may be more important as a loss factor than at Middelplaten.…”
Section: Algal Biomass Distributionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bird grazing takes place mainly during the late summer and autumn when the difference between sites is already evident; thus we assume that grazing was also not responsible for the observed difference. Several authors have suggested the importance of wind and currents as important factors for transport of free-floating macroalgae Hernández et al 1997;Salomonsen et al 1997). In the Veerse Meer, transport from the more exposed site at Kwistenburg may be more important as a loss factor than at Middelplaten.…”
Section: Algal Biomass Distributionmentioning
confidence: 99%
“…weekly to biweekly) it can be assessed whether growth or loss processes determine spatial variation in macroalgal distribution and how growth in its turn correlates to environmental parameters (Sfriso 1995;Hernández et al 1997). Thus far, only few studies have addressed spatial variation in this way (Geertz-Hansen et al 1993;Hernández et al 1997;Sfriso and Marcomini 1997;Barthelemy et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Blooms of green macroalgae have been reported to have a harmful impact on intertidal marine ecosystems in a variety of ways, including changes in ecosystem structure (Raffaelli et al, 1998;Taylor, 1999;Nelson & Lee, 2001) and reduction of biodiversity (Valiela et al, 1997;Raffaelli et al, 1998;Taylor, 1999). Moreover, green tides may also have a deleterious effect on local fisheries and aquaculture industries and may contribute to a decrease in tourism revenue due to the presence of aesthetically displeasing and noxious-smelling deposits of drift weed on shorelines (Hernandez et al, 1997;Taylor, 1999). 'Red tides' (caused by blooms of harmful microalgae) are also occurring with increasing frequency in coastal waters worldwide and cause disastrous damage to the fishery and aquaculture industries of many countries (Qi et al, 1993;Horner et al, 1997;Kim, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Because of the severe ecological and economic problems that result from coastal algal blooms, many investigations have sought the mechanisms that enable these bloom-forming algae to outcompete other coastal primary producers and establish dominant populations. Understanding the mechanisms may be helpful in developing strategies for the control of such harmful algal blooms (Hernandez et al, 1997;Smayda, 1997;Valiela et al, 1997;Taylor et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation